HSV-1 miR-H6 Inhibits HSV-1 Replication and IL-6 Expression in Human Corneal Epithelial Cells In Vitro - Fang Duan; Jingyu Liao; Qiang Huang; Yuhong Nie; Kaili Wu (Clinical and Developmental Immunology)
HSV-1 infection in the cornea could lead to blindness. The infected cell polypeptide 4 (ICP4) of herpes simplex virus 1 (HSV-1) is a regulator of viral transcription that is required for productive infection. It has been previously demonstrated that miR-H6 encoded from HSV-1 genome targets ICP4 to help maintain latency. In this study, synthesized miR-H6 mimics were transfected into HSV-1-infected human cornea epithelial (HCE) cells. The inhibition of HSV-1 replication and viral ICP4 expression in miR-H6-transfected HCE was confirmed by plaque assay, immunofluorescence, and Western blot. Compared to nontransfection or mock, miR-H6 produced a low-titer HSV-1 and weak ICP4 expression. In addition, miR-H6 can decrease the interleukin 6 released into the medium, which was determined by ELISA. Taken together, the data suggests that miR-H6 targeting of ICP4 inhibits HSV-1 productive infection and decreases interleukin 6 production in HCE, and this may provide an approach to prevent HSV-1 lytic infection and inhibit corneal inflammation.